2022
DOI: 10.1155/2022/8798838
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Features and Risk Factors of Fever in Acute Gouty Arthritis

Abstract: Objectives. This study aimed to investigate the clinical characteristics and risk factors of fever in hospitalised patients with acute gouty arthritis (AGA). Methods. The clinical data of 167 hospitalised patients with AGA who met the inclusion criteria were retrospectively analysed. The demographic, clinical, and medication data of patients with and without fever were compared, and risk factors associated with fever were identified via logistic regression analysis. Results. The incidence of fever in hospitali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%